Analisis Kuantitatif Dampak Endorsement Politik Terhadap Tingkat Elektabilitas Pada Pilkada Serentak 2024 - Fristiyanto, Doni; Makhsun (Jurnal Ilmu Komputer, 2024)
Simultaneous Regional Head Elections (Pilkada) in Indonesia took place on November 27 2024, covering 545 regions, including 37 provinces, 415 districts and 93 cities. Voter turnout reached an average of 71% nationally, reflecting public enthusiasm for the political process. This research also highlights the phenomenon of political endorsements from national figures which have proven effective in increasing candidate electability. To explore the phenomenon of political endorsement, this research uses Google News as a tool to collect and analyze relevant online news. The results of the analysis show that there is a significant correlation between the candidate's level of popularity and electability level, with a correlation value of 0.757. Apart from that, the level of positive sentiment towards candidate pairs also shows a strong correlation (0.74) with electability, indicating that candidates with high popularity and positive sentiment tend to have better electability. However, this research found that the number of political endorsements had a stronger influence on candidate electability, with a correlation value of 0.758. This shows that political endorsement can be a more significant determining factor in increasing electability compared to just relying on popularity or positive sentiment. This research provides important insights into the role of political endorsements as an effective strategy in increasing voter support for certain candidates.